Mapping malaria seasonality in Madagascar using health facility data - Nguyen, M; Howes, RE; Lucas, TCD; Battle, KE; Cameron, E; Gibson, HS; Rozier, J; Keddie, S; Collins, E; Arambepola, R; Kang, SY; Hendriks, C; et al. (BMC (part of Springer Nature), 2020)
Background Many malaria-endemic areas experience seasonal fluctuations in case incidence as Anopheles mosquito and Plasmodium parasite life cycles respond to changing environmental conditions. Identifying location-specific seasonality characteristics is useful for planning interventions. While most existing maps of malaria seasonality use fixed thresholds of rainfall, temperature, and/or vegetation indices to identify suitable transmission months, we construct a statistical modelling framework for characterising the seasonal patterns derived directly from monthly health facility data.